Mental distress and associated factors among Aksum University students, Ethiopia: a cross-sectional study - Tesfahunegn, Tadis Brhane (BMC Psychiatry, 2019)
BACKGROUND: Mental distress is becoming a common health problem in Ethiopia. The prevalence of mental distress is higher among university students than the general population. However, there is inadequate information in this regard in Ethiopia situations. The aim of this study was to determine the prevalence and associated factors of mental distress among regular undergraduate students in Aksum University, North Ethiopia. METHODS: An institution based cross-sectional study was carried out among 919 students from May 10 to 20, 2016. Students were selected by stratified multi-stage sampling technique. Data were collected using pre-tested and structured self-administered questionnaire. The collected data were entered into EPI-INFO version 7 and then exported to SPSS version 21 for analysis. Bivariate and multivariate binary logistic regression models were used to determine the factors associated with mental distress among university students. RESULTS: The prevalence of mental distress was nearly four in ten (39.6%) students. Being female sex (AOR =1.7, 95% CI: 1.20, 2.34), low social support (AOR = 3.05, 95% CI: 1.97, 4.72), freshman students (AOR = 1.73, 95% CI: 1.10, 2.71), having had conflict with friends (AOR = 1.5,95% CI: 1.03, 1.90), financial problem (AOR = 2.20, 95% CI: 1.59, 2.92), family history of mental disorder (AOR = 2.10, 95% CI: 1.37, 3.21), scoring lower grade (AOR = 1.51,95% CI: 1.03, 1.61), argument with instructors (AOR = 1.52,95% CI: 1.12, 2.07) and field of study (AOR = 1.56, 95% CI: 1.03, 2.37) were significantly associated with mental distress. CONCLUSION: This study has shown that the magnitude of mental distress among Aksum University students was high. Several social and economic factors were significantly associated with mental distress of the students. Therefore, mental distress needs special focus and timely corrective action by policy makers, university officials, and other concerned stakeholders.